TEN-YEAR PREMORBID BLOOD PRESSURE CONTROL AND WHITE MATTER CHANGES IN A POPULATION-BASED COHORT OF TIA AND STROKE PATIENTS. (29th November 2012) - Simoni, M; Li, L; Mehta, Z; Rothwell, PM
Abstract : Background: White matter changes (WMC) on brain imaging increase with age. The association with hypertension, their risk factor, has been found weaker in the elderly, perhaps because use of only a single baseline or limited number of recent blood pressure (BP) measurements does not reflect longer-term hypertension. The fall in diastolic BP in the elderly may also exacerbate WMC. We determined the association based on all BP measures over 10-years. Methods: In a stroke and TIA cohort, we collected all pre-morbid BPs from primary care. WMC were rated on baseline CT or MRI with four scales, and age-specific associations with BP parameters (mean and max systolic, diastolic and pulse pressure) based on baseline vs 10-year measurements. Results: 1840 patients had MRI (520) and/or CT (1717). Results were similar for CT and MRI, in any of the scales used. Associations between BP and WMC were consistent in patients under 65 years, although 10-year mean was more strongly associated than most recent BP: for example, OR (95% CI) per 10 mm Hg SBP and van Swieten scale—10-year mean=1.37 (1.12–1.68) p=0.002; most recent=1.18 (1.00–1.39) p=0.046. No associations with SBP were significant at age ≥75 years. In contrast, 10-year mean DBP remained positively associated with WMC in the elderly (≥75 years—1.48, 1.19–1.84, p=0.001), with no J-shape. Conclusions: Associations between BP parameters and WMC strengthen when based on multiple BP measures. Although the association with SBP still diminishes with age, there is no evidence that low SBP or DBP are associated with more severe WMC in the elderly.